Densities and Kinematic Viscosities of a Quinary Regular Liquid System and Its Five Quaternary Subsystems at 293.15 K and 298.15 K - Omar, El-Hadad; Ruo, Cai; Abdul-Fattah, A. Asfour (Springer US, 2014)
Densities and kinematic viscosities of a quinary regular liquid system and its five quaternary subsystems were measured at two different temperatures. Pure component properties of the quinary system octane (1) + heptane (2) + ethylbenzene (3) + cyclohexane (4) + toluene (5) have shown excellent agreement with previously reported data.Kinematic viscosity data obtained for different mixtures of this quinary system and its quaternary subsystems were used to test the predictive capability of selected viscosity models available from the literature.